Some Considerations about the Rotating Cell Structure - Franco Nurzia; Chiara Palomba; Pierpaolo Puddu (International Journal of Rotating Machinery)
Rotating stall instability in axial flow compressors arises when the mass flow is reduced at constant rotational speed. Despite the number of experimental and theoretical work already published in the scientific literature, many questions still remain unanswered. A complete model that could be of help both in the design process and in the modelling process of existing engines is not yet available. A fundamental research program has been carried out at the Department of Mechanical Engineering of the University of Cagliari with the scope of reaching a better understanding of the basic flow field structures and of the global performance in stall. The cinematic structure of the cell during abrupt full 1-cell stall in a two-stage axial flow compressor with IGV has been analysed with the aid of hot-wire anemometer and of a total pressure probe. The results have revealed interesting features about the cell flow structures and their variations along the stalled performance branch of the compressor. The present paper aims at pursuing further the flow analysis including the investigation of upstream flow field. Therefore, the inlet duct has been extended to perform the measurements. The complete flow field measurements will allow to obtain a complete cinematic description of the cell.